Sarah James. Hellenistic Pottery: The Fine Wares. Corinth VII.7. pp. 360, with 45 ills, 44 plates, 3 plans, 3 tables. 2018. Princeton NJ: American School of Classical Studies at Athens. ISBN 978-0-87661-077-0, hardcover £150. - Daems, Dries (Journal of Greek Archaeology, 2020)
The latest edition in the Corinth volumes, Hellenistic Pottery: The Fine Wares by Sarah James, is the seventh instalment of the pottery volumes, initiated by Saul Weinberg in 1943. It provides a much-needed extension and revision of the chronology of Hellenistic pottery posited in Roger Edwards’ book Corinthian Hellenistic Pottery, which was published as the third volume in this series in 1975.